Caṇḍī in art and iconography - Mukhopadhyay, Somnath (Agam Kala Prakashan, 1984)
Cult of Chandi, Hindu deity in Bengal; study based on medieval Bengali literature and iconography.
Keywords: Caṇḍī Hindu deity / Cult / India / Bengal; Ikonographie; Candi; Indien; Hochschulschrift